PSYCHOMETRIC VISUAL ANALOGUE SCALE IN ASSESSMENT OF THE STABLE ANGINA SEVERITY AND EFFICACY OF ANTIANGINAL THERAPY - E. V. Solyanik (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To evaluate possibilities of psychometric visual analog scales (VAS) for assessment of the stable angina severity and efficacy of antianginal therapy. Material and Methods. Patients (n=259), receiving different pharmaceutical forms of organic nitrates as antianginal therapy were included into the study. Patients (n=130) treated with retarded form of isosorbide mononitrate were enrolled into the first group. Patients (n=129) treated with isosorbide mononitrate in conventional form or isosorbide dinitrate in moderately long-acting form were enrolled into the second group. Questioning with the "Scales of the patient condition" and Seattle Angina Questionnaire was performed in all patients. Spearman's rank correlation coefficient and Fisher test was used to estimate the relationship of parameters determined with standard questionnaire and the quality of life (QL) level, assessed with VAS. Results. After 3 months the integral QL index increased from 3.5±0.2 to 7.4±0.25 points in the 1st group and from 3.3±0.2 to 6.1±0.22 in the 2nd group. The functional dependence of the integral QL index, determined with VAS, and angina pectoris functional class (FC) was found in the linear regression model for the Fisher test. Integral QL index in the range of 10.0-7.6 corresponds to angina pectoris FC I, 7.5-5.3 to FC II, and 5.2-3.9 to FC III. Integral QL index lower than 3.8 only hypothetically could correspond to angina pectoris FC IV. Conclusion. The VAS clinical  implementation is a simple and demonstrative method that adequately reflects the angina severity and the efficacy of antianginal treatment.